South African Latrunculiidae (Porifera: Demospongiae: Poecilosclerida): descriptions of new species of Latrunculia du Bocage, Strongylodesma Lévi, and Tsitsikamma Samaai & Kelly - Samaai, Toufiek; Gibbons, Mark J.; Kelly, Michelle; Davies-Coleman, Mike (Zootaxa, 2003)
A recent major revision of the Family Latrunculiidae (Demospongiae: Poecilosclerida) recognised four valid genera; Latrunculia du Bocage, Sceptrella Schmidt, Strongylodesma Lévi, and Tsitsikamma Samaai & Kelly, from South Africa. The major diagnostic characters of the Family Latrunculiidae are the possession of discate acanthose microrhabd microscleres called acanthodiscorhabds, or more traditionally, “chessman” spicules, that form a dense palisade in the outer ectosome, a tangential layer of styles or anisostrongyle megascleres below this, and a wispy choanosomal skeleton of the same spicules. The sponge surface almost always has areolate porefields and short fistular oscules. This paper reports new Latrunculiidae from western and southeastern South Africa, including a redescription of Latrunculia biformis (Kirkpatrick). Four key characters, including microsclere ornamentation, spicule dimensions, colouration in life, and surface aquiferous features, define three new species of Latrunculia (L. lunaviridis sp. nov., L. microacanthoxea sp. nov., and L. bellae sp. nov.), two new species of Strongylodesma (S. algoaensis sp. nov. and S. tsitsikammaensis sp. nov.), and two new species of Tsitsikamma (T. pedunculata sp. nov. and T. scurra sp. nov.).